2005
DOI: 10.1016/s0210-4806(05)73195-8
|View full text |Cite
|
Sign up to set email alerts
|

Aplicaciones clínicas de la teoría integral de la continencia

Abstract: Currently, urinary incontinence cannot be treated without taking into consideration the comprehensive theory of urinary incontinence. According to this theory, stress incontinence, urge incontinence and alterations in bladder emptying result from alterations in the elements of suburethral support, ligaments and muscles of the pelvis floor. Alterations in the forces applied by muscles and ligaments to the fascia adjacent to the vaginal wall and the urethra cause the vesical neck and the urethra to open or close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
3
0
3
Order By: Relevance
“…According to the integral theory, an imbalance in the pelvic floor force lines can trigger “de novo” prolapse. 19 In our series, only 10% of patients presented a worsening of their posterior compartment POP-Q stage (“de novo” prolapse), going from stage 0 to stage I (Ap-3 to Ap-2), without any symptoms and without requiring intervention in any case. These data are similar to those for PL (9.5%) 4 and SLL (12%).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…According to the integral theory, an imbalance in the pelvic floor force lines can trigger “de novo” prolapse. 19 In our series, only 10% of patients presented a worsening of their posterior compartment POP-Q stage (“de novo” prolapse), going from stage 0 to stage I (Ap-3 to Ap-2), without any symptoms and without requiring intervention in any case. These data are similar to those for PL (9.5%) 4 and SLL (12%).…”
Section: Discussionmentioning
confidence: 58%
“…Functionally, LA significantly improves 22% of the symptoms of overactive bladder measured by the OAB-SF questionnaire. This may be because the LA repositions the vaginal vault in all patients, and according to the integral theory, apical prolapse, even of a small magnitude, may be responsible for the clinical filling 19 . On the other hand, LA is a safe technique with 0% intraoperative complications and 5% postoperative Clavien III complications, comparable to other techniques for the repair of POP 4,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Riccetto et al .,[9] suggested that the principal ligaments of the pelvic floor that interact with the muscles during Valsalva maneuver are: (1) Pubo-urethral ligaments (PUL), which originate from the lower border of pubis, pass downward and insert into the arcus tendineus fascae pelvis (ATFP) on the level of mid-urethra; (2) urethro-pelvic ligaments (UPL), which originate bilaterally from the above mentioned insertion of PUL into ATFP and fuse behind the mid-urethra; (3) utero-sacral ligaments, which originate from the sacrum, pass forward and insert into the vaginal Halban's fascia, making a fascial ring around the uterine cervix. The region between the mid-urethra and urethra-vesical junction, so-called zone of elasticity, plays a crucial role in the urination-continence mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…En 1996 Ulmstem, introduce la técnica de TVT (Tensión free vaginal tape) que se caracteriza por ser una intervención mínimamente invasiva, con una fácil y rápida ejecución, corto tiempo operatorio y baja incidencia de complicaciones, presentando resultados comparables a la colposuspensión, incluso a largo plazo. 8,9 Las tasas de complicaciones del 35% de las mallas condujeron a desarrollar nuevas técnicas que conserven los atributos del TVT, pero con menores complicaciones, por eso surge en 2001 el TVT por el agujero obturador (TOT), caracterizándose por ser una técnica sencilla, fácil de aprender y con una baja tasa de complicaciones (1.1%). 10,11,12 Las intervenciones quirúrgicas para la IUE tienen tres resultados posibles: En primer lugar, que el tratamiento no dé suficiente aumento a la resistencia uretral y que la paciente siga teniendo fugas durante eventos de esfuerzo, en la cual, la paciente sería capaz de orinar con normalidad, pero seguiría siendo incontinente.…”
Section: Incontinencia Urinaria De Esfuerzo (Iue)unclassified